Implementasi Pembelajaran Kontekstual Berbasis Masalah Dalam Pembelajaran Ilmu Pendidikan Islam - Muslihan, Muslihan; Hakim, Abdul Azizul (FAKULTAS TARBIYAH, 2021)
This study aims to determine the effectiveness of the implementation of problem-based contextual learning strategies in an effort to improve the quality of the learning process, improve learning outcomes, absorbency, and mastery of student learning, and determine student responses to the application of problem-based contextual learning strategies. The research was conducted using classroom action research methods and the implementation of the learning process was carried out in four cycles. The research was conducted on fourth-semester students of Islamic Economic Law STIS Harsyi Central Lombok in the 2019/2020 academic year. Data on the quality of the learning process and student responses were recorded using a questionnaire with a 5-level Likert scale. Data on student learning outcomes were collected by providing an assessment of solving tasks, mid-semester exams, and end-of-semester exams. The average score for the assessment of the quality of the learning process reached 4.07, including the good to very good category. Student learning outcomes show a good category with the average final grade of students being 7.54, absorption capacity reaching 75.4%, and learning completeness reaching 87.5%. Assessment of student perceptions shows that students are responsive to the implementation of problem-based contextual learning strategies with an average score of 4.19. Problem-based contextual learning strategies are able to develop and optimize students' abilities so that there is an increase in students' abilities in solving Islamic Religious Education problems which are implemented in the Islamic Religious Learning program.